Training of engineering research students: approach to the state of the art (Nexo Revista Científica, 2021)
The current literature review aims to identify the current situation presented by research in the engineering environment, specifically in the formation of this competence in higher education students in Mexico, ranging from the educational process to the investigative, with the purpose of reporting the progress made in this country, since such situations directly influence the development of multiple factors. Through a documentary review, it delved into the methods and ways in which it is tried to teach the competence of research in young university students in Latin America, to later contrast its reality with that of Mexico. The foregoing made it possible to know the opinions and progress that have been achieved in the field of research, particularly in the development of investigative competence in Higher Education Institutions in the study area, as well as the actors involved in this noble task of generating and spread knowledge. Finally, teaching to know how to investigate requires the development of capacities, critical analysis, ethical duty and commitment to society that make it possible to clarify the requirements and adverse situations that education currently has.